Novel entry pathways for Hepatitis B virus - Parmar, Devan (2023)
Hepatitis B virus (HBV) is a global health problem. Patients with chronic hepatitis B (CHB) infection can develop progressive liver disease, including cirrhosis and hepatocellular carcinoma (HCC). There is still much to understand about the molecular biology of HBV, particularly viral entry. The main entry receptor of HBV is sodium taurocholate cotransporting polypeptide (NTCP); however, a variant of HBV, BT10D4 has recently been discovered, that infects cells independent of NTCP expression. This study aimed to demonstrate NTCP-independent infection by BT10D4 and to elucidate the alternative receptor involved in entry of this variant. The methodology used to investigate the entry receptor is known as pseudotyping, a technique utilised to produce ‘customized’ chimeric viruses that possess envelope glycoproteins that are not encoded by the viral genome. In this case, the pseudotype has an HBV glycoprotein and a HIV-1 capsid containing a luciferase reporter gene, allowing quantification of infection into susceptible cells. Pseudotypes were used to infect the hepatoma cell line Huh7, and Huh7 cells induced to express NTCP. The pseudotype assays clearly demonstrated that BT10D4 facilitated NTCP-independent infection. Furthermore, the receptor annexin A2 was identified as a candidate for BT10D4 entry. Neutralisation and binding assays using anti-annexin A2 and soluble annexin A2 were performed. Whilst statistical analyses showed no significant change in infection, Huh7.NTCP cells pre-treated with anti-annexin A2 and infected with BT10D4 showed a reduction in infectivity, as the concentration of anti-annexin A2 increased. The inhibition assay was repeated using the soluble form of annexin A2 but showed no resolvable inhibition or trend. However, it is important to note that the conformation of the soluble form of annexin A2 could be different to its conformation on the cell surface. Annexin A2 doesn’t not appear to be an entry receptor for HBV and further studies should be performed to identify alternative candidates, which would aid in the development of novel therapeutic strategies to combat HBV entry that is NTCPindependent.